Undergraduate Students’ Difficulties in Mastering Research Methodology Course in Islamic Higher Education - Erlinda, Rita; Darmayenti; Dewi, Merry Prima (Journal of Education Reseach and Evaluation, 2022)
In general, undergraduate students perceived Research Methodology course as a complex subject. The present study aims to find out undergraduate English Teaching Department students’ opinion on the implementation of Research Methodology course, students’ difficulties in mastering the topics of Research Methodology course, and factors affecting their difficulties in comprehending Research Methodology course in three State Islamic higher education in West Sumatera, Indonesia. The study was survey research with cross-sectional design. One hundred twenty-five active students enrolled in Research Methodology subjects participated in this study. Questionnaires were used to collect the data. The findings revealed that 66.65% students perceived that the Research Methodology course implemented properly; 67.74% students perceived that they comprehended quantitative research topics and 65.56% qualitative research topics; 75.30% students perceived that Research Methodology was a complex course; and dominant factor causing students’ difficulties in comprehending learning materials/topics was teaching and learning process (40.00%). It implies that a new and innovative teaching model should be developed by the lecturers in order to gain the aims of Research Methodology course and to help the students to be better in the learning engagement, critical thinking and research skills.